2012
DOI: 10.1074/jbc.m111.314922
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Estrogen-induced miRNA-29 Expression in Carbon Tetrachloride-induced Mouse Liver Injury

Abstract: Background: Mechanism underlying the protection of estradiol against CCl 4 -induced hepatic fibrosis remains unclear. Results: miR-29 expression was differentially regulated in male/female mice during CCl 4 treatment. Both estradiol and miR29a/b-expressing adenovirus increased hepatic miR-29a/b levels and attenuated CCl 4 -induced hepatic fibrosis. Conclusion: Estradiol inhibits CCl 4 -induced hepatic injury via inducing miR-29a/b. Significance: Learning the role/regulation of miR-29 in hepatic fibrosis and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…Other investigators reported the modulation of other miRNAs by glucocorticoids and TGF-b. 38,39 Although the mechanism underlying the regulation of miR-30 by glucocorticoids or TGF-b remains unknown at this stage, our previous finding that TGF-b reduces miR-29a/b level in IAR20 cells through increasing the level of nuclear NF-kB p65 40 may imply that TGF-b can also reduce miR-30 level via upregulating the NF-kB signaling pathway in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators reported the modulation of other miRNAs by glucocorticoids and TGF-b. 38,39 Although the mechanism underlying the regulation of miR-30 by glucocorticoids or TGF-b remains unknown at this stage, our previous finding that TGF-b reduces miR-29a/b level in IAR20 cells through increasing the level of nuclear NF-kB p65 40 may imply that TGF-b can also reduce miR-30 level via upregulating the NF-kB signaling pathway in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-29 family contains three members miR-29a, miR-29b, and miR-29c, all of which are transcriptionally induced by p53 [68] and repressed by c-Myc, NF-κB, and TGF-β signaling ( see [69]). Functionally, miR-29 serves to reduce cell proliferation by targeting CDK6 [7071], to induce cell senescence or differentiation by targeting Ppmid [68] or osteonectin [72], respectively, and to stimulate cell apoptosis by targeting Mcl1 and Bcl2 [7374].…”
Section: Regulation Of Mirnas In Carcinomasmentioning
confidence: 99%
“…Xu et al [32] have reported that E 2 suppressed HSC proliferation and was paralleled by the inhibition of TGF-b1 and PDGF expression in CCl 4 -induced fibrosis in male and female rats. The induction of miR-29a and miR29b expression by E 2 was opposite to the effect of TGF-b1 [46].…”
Section: Micrornas and Gene Expression In Estrogen-dependent Functionsmentioning
confidence: 95%
“…Zhang et al [46] have reported the role of estrogen-induced miR-29 expression in CCl 4 -induced mouse liver injury. The levels of miR29a and miR-29b expression were significantly decreased in the livers of male, but not female mice, and the downregulation of miR-29a and miR-29b correlated with the early development of hepatic fibrosis.…”
Section: Micrornas and Gene Expression In Estrogen-dependent Functionsmentioning
confidence: 99%
See 1 more Smart Citation